The Lukan lens on wealth and possessions : a perspective shaped by the themes of reversal and right response - Coleman, Rachel L., (On (De)Coloniality: Curriculum Within and Beyond the West, 2020)
In The Lukan Lens on Wealth and Possessions: A Perspective Shaped by Reversal and Right Response, Rachel Coleman offers a detailed look at Luke's wealth ethic. The long-debated question of how Luke understands the relationship between followers of Jesus and material possessions is examined with careful exegesis and keen literary and theological sensitivity. The twin motifs established in Luke's introductory unit (Luke 1:5-4:44)-reversal and right response-provide the hermeneutical lenses that allow the reader to discern a consistent Lukan perspective on wealth in the life of disciples. With an engaging style and an eye to the contemporary church, the book will appeal to both scholars and pastors.